Adaptive Virtual Partitioning: Further Developments - Lima, Alexandre A. B.; Mattoso, Marta; Valduriez, Patrick (Journal of Information and Data Management, 2010)
Adaptive Virtual Partitioning (AVP) is a parallel query processing approach which gracefully adapts to load unbalancing. This paper describes the further developments on AVP after the initial proposal.